Seed orchards in Poland - Kowalczyk, Jan; Rzońca, Marek (Studia Ecologiae et Bioethicae, 2018)
Polish forests have multiple functions, from the provision of spaces for leisure and recreation and conservation of nature and biodiversity to the creation of wealth and employment and the production of natural resources and raw materials for industry and bioenergy production. This multi-functionality creates conflicts between different uses and stakeholders. As the durability of wood use is inextricably linked to tree breeding, the basic tool for accomplishing these tasks is breeding programmes for forest trees, and one of the important elements in tree breeding activities is the seed orchards. In this review article, we present the state of the art of seed orchards in Poland and their grouping according to importance in forest management. We include historical facts regarding the creation of the idea of seed orchards and its implementation in forest breeding practice. When we manage seed orchards, on the one hand, we care about genetic variability, and on the other hand, we aim for genetic gain. Seed orchards are effective and economically viable for their role in forestry. According to economic studies, the increase in seedling production costs in connection with the use of seeds from seed orchards, does not exceed 3%. According to the authors, seed orchards are the most rational and least ecologically risky way to improve forest production.